PEMANFAATAN MEDIA SOSIAL DALAM PROSES PEMBENTUKAN OPINI PUBLIK (ANALISA WACANA TWITTER SBY) - Fauzi Syarief (Universitas Bina Sarana Informatika, 2017)
Problem in this research is how the formation of public opinion by making use of social media presence, this study aims to find out how social media utilized in the formation of public opinion in this case twitter account @SBYudhoyono. This research using the method of discourse analysis. SBY twitter account can be analyzed how the sentence form, grammar, semantics, and vocabulary used in SBY twitter account, so as to give rise to publik opinion.Of this results it is concluded that a text can cause a wide range of public opinion so the management must pay attention to social media instruments in the creation of a text or sentence.Key word: the use of social media, public opinion.